Immunomodulatory Activity of Agarwood Aquilaria malaccensis Lamk. Leaf Extracts on Staphylococcus aureus-infected Macrophages in vitro - Hiqmah Yusi Yana; Lisna Hidayati; Nastiti Wijayanti; Tri Rini Nuringtyas (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Aquilaria malaccensis has been consumed as herbal medicine, and in vitro study showed that the leaf extract possesses high antioxidant activities. A brief preliminary study indicated that A. malaccensis showed a promising immunomodulatory activity when evaluated using latex beads. This current study aimed to evaluate the immunomodulatory activity of A. malaccensis leaf extract on the macrophage, which was challenged with pathogenic bacteria Staphylococcus aureus.METHODS: Bioactivity was determined by evaluating the phagocytic capacity of macrophages isolated from Mus musculus against S. aureus. First, the cytotoxicity of extracts on macrophages was evaluated using MTT assays, and the IC50 value was used to determine the dose of immunomodulatory assays. The highest toxicity was observed on chloroform extract with an IC50 value of 111.4 µg/mL. Therefore, the treatment was 100 and 50 µg/mL. Two parameters, including the phagocytic activity and phagocytic capacity of macrophages infected with S. aureus, were used to evaluate immunomodulatory activity. The analysis of variance was done at p<0.05 to determine the significant difference among treatments.RESULTS: Chloroform and ethanol extracts at a 50 µg/mL concentration showed the best results with the phagocytic activity of 82.33%±9.61% and 80.33±1.53%. The ethyl acetate showed lower phagocytic activities of 70.67±1.53. All extracts significantly increased phagocytic activity and phagocytic capacity, and the results differed significantly between negative and positive controls. Thin-layer chromatography indicated that the extract contained terpenoid, flavonoid, phenolic, and tannin.CONCLUSION: A. malaccensis leaf extracts showed immunomodulatory activity. Both chloroform and ethanol extracts showed comparable activity, while the ethyl acetate extract was lower. The extracts contained diverse bioactive compounds that may support activating macrophage cells for immunomodulatory activity.KEYWORDS: Aquilaria malaccensis, immunomodulator, phagocytosis, macrophages, Staphylococcus aureus